Determinación del incremento del rendimiento en 18 variedades de trigo (Triticum aestivum) provenientes del banco de semillas del INIAP-Santa Catalina en la localidad de Naguán, provincia Bolívar - Guambuguete Guambuguete, Bélgica Olimpia (2022)
Wheat is one of the agricultural products considered essential and basic as a food source worldwide. Wheat production in our province is vital, for utilization and economic retribution; however, the yields obtained in the province are generally low due to different biotic and abiotic factors. The specific objectives proposed in this research were: To evaluate the morphological characteristics of 18 improved wheat varieties from INIAP, cultivated in the agro-ecological zone of Naguan; To know the agronomic characteristics and quality of 18 improved wheat varieties from INIAP; To identify the productive potential of the best wheat varieties for the agro-ecological zone under study. Complete Blocks at random (DBCA) with 3 replications were used, and the following was performed: Functional Statistical Analysis, Tukey's test to compare the averages of the treatments and correlation and linear regression analysis, the 18 varieties of wheat, it was recorded that 50% presented an erect habit, likewise the other 50% presented an intermediate habit (Semi-erect or semi-prostrate). In the grain type descriptor, 39% of the varieties showed a large, large, well-formed, clean grain, 44% showed a medium, wellformed, clean grain, and the last one corresponding to 17% of the varieties showed a small, thin, spotted, sucked grain. The best yields were obtained in the varieties; T14: INIAP-ZHALAO 2003 with 8020.9 kg/ha, and T11: INIAP-QUILINDAÑA 94 with 7585.5 kg/ha, while the varieties; T16: INIAP-SAN JACINTO 2010 with 5499.1 kg/ha and T7: INIAP-ALTAR 82 with 5183.1 kg/ha, were the ones that obtained the lowest averages. The agronomic components that helped to increase the yield of the wheat crop were; Number of spikes per linear meter, Number of grains per spike, Yield per plot, Weight of thousand grains, hectoliter weight, while the variable that reduced the yield was; Reaction to foliar diseases.